Isolation and Identification of Dermatophytes Causing Dermatophytosis at a Tertiary Care Hospital in Bangladesh - SA, Khan; SM, Shamsuzzaman; AKMS, Rahman; NAK, Ashekin; R, Mahmud; R, Sharmin; MRU, Siddique; MA, Khan; S, Sultana; F, Haque (Archives of Clinical and Biomedical Research, 2021)
Background: Dermatophyte, a keratinophilic fungus which can invade keratinized tissue cause dermatophytosis. It is one of the major superficial fungal infections. According to World Health Organization (WHO), 20-25% world population is affected by dermatophytes. The aim of this study was to identify different species of dermatophytes causing dermatophytosis at a tertiary care hospital in Bangladesh. Methods: Total 246 skin, nail and hair samples were collected from Dermatology and Venereology department of Dhaka Medical College Hospital (DMCH), Dhaka, Bangladesh. Dermatophytes were identified by microscopy, culture, biochemical test (urease test and hair perforation test) and polymerase chain reaction (PCR). Fungal elements were observed under microscope. Sabouraud Dextrose Agar (SDA) and Dermatophyte Test Medium (DTM) were used to culture the specimen. Species identification was confirmed by biochemical test and PCR. Results: Among 246 clinically diagnosed cases of dermatophytosis, 91 (36.98%) cases were observed among the age group of 21-30 years. Female were more affected than male (male-female ratio was1:1.34). Eighty-five (34.55%) cases were positive by microscopy and 76 (30.89%) cases were positive in culture. Trichophyton mentagrophyte was the common etiological dermatophyte species which was 59.21% followed by Trichophyton rubrum (40.79%). All culture isolates were further evaluated by biochemical test and PCR. Most of the tinea corporis was caused by Trichophyton mentagrophyte which was 64.81%. Conclusion: Dermatophytosis is a common infection in young adults specially females. Trichophyton mentagrophyte is more frequent type of dermatophyte. Majority of dermatophytes could be identified by both direct microscopy and culture methods.